STRUKTUR PENGETAHUAN YANG MEMPENGARUHI DECISION/ACTION PADA ATLET PANAHAN : CONTEXT REVIEW - Utama, Dio Kevin Alief Utama; Subagio, Irmantara; Setijono, Hari (Journal of Sport and Exercise Science, 2023)
The role of psychology in sports is very much needed in achievement sports, especially archery, where many athletes often experience psychological problems during championships or during training sessions. The purpose of this study is to discuss the knowledge structure or factors that influence decisions/actions in archery athletes, using the context review analysis method cited from relevant research results. Reviews in this study examine the results of pre-existing research cited from international journals such as PubMed, Springer, ScienceDirect and Journals from various universities in Indonesia. The results of this study found that there are several factors that can indeed be studied and can influence decisions/actions in archery athletes that can be used and added to team/club training programs to overcome psychological problems experienced by athletes. In conclusion, there are six main factors that influence the decision/action of athletes. It is hoped that these main factors can be applied to athlete training programs as support for performance when practicing or during competition.